How does community-managed infrastructure scale up from rural to urban? An example of co-production in community water projects in Northern Pakistan. (October 2021) - Birkinshaw, Matt; Grieser, Anna; Tan, Jeff
This paper examines the role of participation, co-production and community management in a random sample of 50 rural and urban water systems under the Water and Sanitation Extension Programme (WASEP) in Gilgit-Baltistan, Pakistan. It looks at the role of an NGO (the Aga Khan Agency for Habitat) in co-production, and how this model of community-based water management (CBWM) contributes to the discussion in the literature. Specifically, the paper considers whether the largely rural WASEP model can be successfully scaled up and scaled out to urban centres, drawing on evidence from a survey of over 2, 500 rural and urban households. The findings illustrate the importance of participation in the successful delivery of water systems. However, higher levels of rural participation are related to specifically rural features, including the smaller size and more limited diversity of communities. The paper concludes that new methods may be required for the transfer of CBWM to urban centres with much larger, more diverse and growing populations.